An Efficient Synthesis of Highly Functionalized and Electron-Deficient 1,3-Dienes from Cyclobutene Derivatives - BAHARFAR*, R.; VAHDAT, S.M.; BAGHBANIAN, S.M. (Asian Journal of Chemistry, 2024)
Cyclobutene derivatives undergo electrocyclic ring-opening reactions in boiling toluene to produce highly electron-deficient 1,3-dienes. These cyclobutenes prepare from the reaction of 2-thenoyltrifluoroacetone in presence of triphenyl phosphine at room temperature, via intramolecular Wittig reaction.